Home business tax deductions 2025 : keep what you earn - Fishman, Stephen (Nolo, 2025)
"For any home business, claiming all the tax deductions you are entitled to is essential to your business's financial success. Don't miss out on the many valuable deductions you can claim. Here, you'll find out how to deduct: start-up costs, home office expenses, vehicles, meals, and travel expenses, medical expenses, and retirement expenses. Easy to read and full of real-life examples, this book can help you take advantage of all the valuable deductions you are entitled to"--